PENINGKATAN KETERAMPILAN MEMASAK MELALUI PELATIHAN HIBACHI - Moch Nur Efendi; A.A. Ayu Suwi Arianty; Luh Eka Susanti (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The Community Service Program through hibachi training aims to improve competency, creativity, and innovation in food presentation. The study used a qualitative descriptive approach through field studies and participant observation. The results showed that the hands-on training method (learning by doing) improved participants' understanding of the concept of Hibachi cooking, thereby providing a memorable dining experience. The conclusion of this activity is that practice-based training has proven effective in improving cooking skills and mastering hibachi tricks. Recommendations include continuing the training program periodically, providing mentoring during training, creating hibachi competitions, and collaborating with other learning programs. This training model can be replicated on campus or other culinary training facilities with similar potential as a strategy to improve knowledge and skills in the culinary field.